2021
DOI: 10.1371/journal.pgen.1009583
|View full text |Cite
|
Sign up to set email alerts
|

RIOK2 phosphorylation by RSK promotes synthesis of the human small ribosomal subunit

Abstract: Ribosome biogenesis lies at the nexus of various signaling pathways coordinating protein synthesis with cell growth and proliferation. This process is regulated by well-described transcriptional mechanisms, but a growing body of evidence indicates that other levels of regulation exist. Here we show that the Ras/mitogen-activated protein kinase (MAPK) pathway stimulates post-transcriptional stages of human ribosome synthesis. We identify RIOK2, a pre-40S particle assembly factor, as a new target of the MAPK-act… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…RIOK2 belongs to the family of RIO kinases, which comprises three members: RIOK1, RIOK2, and RIOK3 (LaRonde- LeBlanc and Wlodawer, 2005). RIO kinases play a role in pre-ribosomal RNA processing and the biogenesis of ribosomes (Cerezo et al, 2021). The miRNA-TF-mRNA regulatory network.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RIOK2 belongs to the family of RIO kinases, which comprises three members: RIOK1, RIOK2, and RIOK3 (LaRonde- LeBlanc and Wlodawer, 2005). RIO kinases play a role in pre-ribosomal RNA processing and the biogenesis of ribosomes (Cerezo et al, 2021). The miRNA-TF-mRNA regulatory network.…”
Section: Discussionmentioning
confidence: 99%
“…RIOK2 belongs to the family of RIO kinases, which comprises three members: RIOK1, RIOK2, and RIOK3 ( LaRonde-LeBlanc and Wlodawer, 2005 ). RIO kinases play a role in pre-ribosomal RNA processing and the biogenesis of ribosomes ( Cerezo et al, 2021 ). The role of RIO kinases in cancer has been increasingly investigated, with the RIOK2 ATPase activity essential for cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…So, we speculated that it might play a crucial role via interacting with RIOK2 for responses to DON exposure. A recent study suggested that RIOK2 is a new target of the MAPK-activated kinase RSK [ 39 ]. As components of the MAPK signaling pathway, ERK and JNK are associated with the regulation of cell survival and death [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cell lysates were prepared as previously described 77 . Briefly, cells were washed three times with ice-cold phosphate-buffered saline (PBS) and lysed in RIPA or BLB buffer (10 mM K 3 PO 4 , 1 mM EDTA, 5 mM EGTA, 10 mM MgCl 2 , 50 mM β-glycerophosphate, 0.5% Nonidet P-40, 0.1% Brij 35, 0.1% deoxycholic acid), complemented with 1 mM sodium orthovanadate [Na 3 VO 4 ], 1 mM phenylmethylsulfonyl fluoride, and a cOmplete protease inhibitor cocktail tablet (Roche).…”
Section: Methodsmentioning
confidence: 99%